Analisis Pendapatan Petani Kentang Pada Program Food Estate Desa Ria-Ria Kecamatan Pollung Kabupaten Humbang Hasudutan - Banjarnahor, Yohanes Syahputra; Dalimunthe, Apip Gunaldi; Safitri, Sri Ariani (Universitas Medan Area, 2025)
This study aims to maintain the economic, social, and political stability of a country and ensure that high-quality food is available, accessible to all people and increased domestic production. The problem is focused on the Indonesian Government launching a National food barn development strategy to overcome the food crisis through the